Lithium ion battery silicon-based negative plate and preparation method thereof

By constructing a double-layer cladding of LATP and organic conductive polymer on the silicon-based anode sheet of lithium-ion batteries, the problem of easy aggregation and poor conductivity of Si particles during recycling is solved, and the cycle stability and electrochemical performance of the anode material are significantly improved.

CN119905526APending Publication Date: 2025-04-29SHANXI PENGRUI RUNZE TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510095962.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The silicon-carbon composite anode material has low cyclic stability under long-term use, and Si particles are prone to aggregation and separation from the conductive carbon matrix, resulting in electrical contact failure and capacity attenuation.

Method used

A double-layer cladding layer was constructed on the surface of nano Si particles. The first layer was an inorganic Li1.3Al0.3Ti1.7(PO4)3 (LATP), and the second layer was an organic conductive polymer cracking layer, which was achieved by sol gel and low-temperature cyclization process.

Benefits of technology

Effectively suppress the volume change of Si negative electrode during the circulation process, enhance the electron and ion transmission between Si particles, and improve the electrochemical performance and cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905526A_ABST
    Figure CN119905526A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-based negative plate of a lithium ion battery and a preparation method of the silicon-based negative plate. The preparation method comprises the following steps: S1, adding silicon powder into a ball mill for ball milling to obtain nano silicon; s2, mixing raw materials of nano silicon and Li1. 3Al0. 3Ti1. 7 (PO4) 3 in a solvent, heating and stirring until the solvent is completely evaporated after mixing, and carrying out heat treatment on an obtained solid sample to obtain a Si-coated LATP single-layer coating material; and S3, fully mixing the Si-coated LATP single-layer coating material and polyacrylonitrile in a solvent to obtain slurry, blade-coating the slurry on a copper foil by using a scraper, drying to completely evaporate the solvent, and then performing heat treatment to obtain the Si-coated LATP-coated C negative plate. The uniform double coating layers are constructed on the surfaces of the nano Si particles through a sol-gel method and a low-temperature cyclization method, and the two coating layers have a synergistic effect, so that not only can the side reaction of an interface be slowed down, but also the electron transmission between the mutually connected Si particles can be remarkably enhanced, and the electrochemical performance and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-based negative electrode sheet for a lithium ion battery and a preparation method thereof. Background Art

[0002] Silicon material has high specific capacity (3575mAh / g), suitable discharge platform (~0.4V vs.Li / Li + ), abundant reserves and environmental friendliness. Therefore, silicon is considered to be the most promising new type of lithium-ion battery negative electrode material. However, silicon (Si) itself has poor conductivity, which is not conducive to the charge transfer of the electrode, and the huge volume expansion effect after Si lithiation leads to poor cycle performance of Si. Therefore, improving the volume expansion of silicon materials and improving their stability have become the focus of attention.

[0003] An effective method to improve the volume expansion of Si materials is to disperse nano-silicon particles into a carbon matrix to develop a high-performance silicon-carbon composite negative electrode. The carbon matrix includes low-dimensional carbon materials such as graphene, carbon nanotubes and carbon fibers with good mechanical properties. The carbon matrix plays a vital role in slowing down the volume change of silicon and improving conductivity. However, due to the weak interaction between Si and the carbon matrix, Si particles are easily aggregated and separated from the conductive carbon matrix material under repeated expansion and contraction behavior, which leads to electrical contact failure and silicon particle crushing, resulting in decreased cycle stability. Especially for silicon-carbon composite materials with high silicon content, the combination between Si materials and carbon matrices still faces great challenges in further suppressing the capacity decay of electrode materials. Therefore, it is particularly important to develop effective preparation technology to achieve good contact between Si nanoparticles and carbon materials in a uniformly distributed manner. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium-ion battery silicon-based negative electrode sheet and a preparation method thereof, so as to solve the problem that the silicon-carbon negative electrode material prepared by mixing Si particles and carbon matrix has low cycle stability under long-term use. The present invention can construct a uniform LATP / C mixed coating on the surface of nano-Si particles through this method, wherein Li 1.3 Al 0.3 Ti 1.7(PO4)3(LATP) has a strong PO covalent bond, which can provide high structural stability for the core Si and effectively inhibit the volume change of the silicon negative electrode during the cycle. Polyacrylonitrile (PAN)-based cracked carbon has high oxidation resistance and fills the gaps between LATP-coated particles, which can alleviate side reactions at the electrode-electrolyte interface. In the preparation process of the negative electrode sheet, the conductive polymer PAN acts as a binder and a conductive agent at the same time, adhering to the entire surface of the silicon particles through in-situ polymerization, thereby forming a more stable conductive network. The silicon-based negative electrode sheet exhibits excellent specific capacity and good cycle stability, and is considered to be an ideal negative electrode material for lithium-ion batteries.

[0005] To achieve the above object, the present invention provides a method for preparing a lithium ion battery silicon-based negative electrode sheet in a first aspect, comprising the following steps:

[0006] S 1: Add silicon powder into a ball mill and grind to obtain nano silicon;

[0007] S2: Nano-silicon and Li 1.3 Al 0.3 Ti 1.7 The raw materials of (PO4)3 are mixed in a solvent, and after mixing, they are heated and stirred until the solvent is completely evaporated, and the obtained solid sample is heat-treated to obtain a Si@LATP single-layer coating material;

[0008] S3: The Si@LATP single-layer coating material and polyacrylonitrile are fully mixed in a solvent to obtain a slurry, and then the slurry is scraped onto a copper foil using a scraper, dried to completely evaporate the solvent, and then heat treated to obtain a Si@LATP@C negative electrode sheet.

[0009] In order to solve the problem that the negative electrode material formed by mixing silicon and carbon matrix in the prior art will have Si particles aggregate and separate from the conductive carbon matrix during the recycling process, thereby causing electrical contact failure, silicon particle crushing, and decreased cycle stability, the present invention specifically proposes a technical solution of double-layer coating on the surface of nano-silicon, wherein the first layer of coating material is an inorganic Li 1.3 Al 0.3 Ti 1.7(PO4)3(LATP), LATP is a high ion conductor. When wrapped on the surface of Si particles, it can promote the transmission of ions inside the electrode. At the same time, LATP has a strong PO covalent bond, which can provide high structural stability for the inner core Si and effectively inhibit the volume change of the silicon negative electrode during the cycle. The second layer of coating material is an organic carbon layer. The outer layer of carbon can fill the gaps between the LATP coated particles, isolate the physical contact between the electrode and the electrolyte, and slow down the occurrence of interfacial side reactions. The organic / inorganic double-layer coating of the present invention cleverly enhances the electron and ion transmission between the interconnected Si particles, thereby improving the electrochemical performance of the battery. In addition, the two coating layers in the present invention work synergistically with each other to improve the cycle stability of the negative electrode material.

[0010] Preferably, in step S1, the silicon powder is at least one of industrial waste silicon, micron-sized silicon powder and nano-sized silicon powder; the particle size of nano silicon is 100-200 nm; during the ball milling process, the mass ratio of ball milling beads to silicon powder is (15-20):1, the ball milling speed is 400-600 rpm, and the ball milling time is 10-12 h.

[0011] Preferably, in step S2, nano-silicon and Li 1.3 Al 0.3 Ti 1.7 The specific process of mixing the raw materials of (PO4)3 in the solvent is as follows:

[0012] LiNO3, Al(NO3)3·9H2O, C 12 H 28 O4Ti and H3PO4 are dissolved in anhydrous ethanol and magnetically stirred at room temperature to obtain a LATP precursor solution. Nano-silicon is then added to the LATP precursor solution, ultrasonically stirred to evenly disperse the nano-silicon in the solution, and then heated and magnetically stirred until the anhydrous ethanol is completely evaporated.

[0013] Preferably, in step S2, nano-silicon and Li 1.3 Al 0.3 Ti 1.7 The specific process of mixing the raw materials of (PO4)3 in the solvent is as follows:

[0014] LiNO3, Al(NO3)3·9H2O, C 12 H 28 O4Ti, H3PO4 and nano-silicon are dissolved in anhydrous ethanol, and magnetic stirring is performed at room temperature combined with ultrasound to make the nano-silicon dispersed evenly in the solution, and then heating and magnetic stirring are performed until the anhydrous ethanol is completely evaporated.

[0015] More preferably, in step S2, the ultrasonic dispersion time is 30 to 60 min, the temperature of the heating magnetic stirring is 60 to 80° C., the rotation speed is 500 to 700 rpm, and the time is 10 to 12 h.

[0016] Preferably, in step S2, LiNO3, Al(NO3)3·9H2O, C 12 H 28 The molar ratio of O4Ti and H3PO4 is 1.3:0.3:1.7:3; LiNO3, Al(NO3)3·9H2O, C 12 H 28 The mass ratio of the total mass of O4Ti and H3PO4 to the mass of nano-silicon is (1-10): (90-99).

[0017] Preferably, in step S2, the heat treatment temperature is 600-800°C, the heating rate is 3-8°C / min, and the holding time is 3-5h.

[0018] Preferably, in step S3, the mass ratio of Si@LATP single-layer coating material to polyacrylonitrile is (2-4):1.

[0019] Preferably, in step S3, the heat treatment temperature is 250-350°C, the heating rate is 3-8°C / min, and the holding time is 1-3h.

[0020] In the preparation of the second coating material organic conductive polymer cracking layer, the present invention uses polyacrylonitrile (PAN) as a raw material and does not use a high heat treatment temperature. This is mainly because the present invention is different from the point contact between the conventional conductive carbon and the silicon material. PAN adheres to the entire surface of the Si particles by in-situ cyclopolymerization, thereby forming a more stable conductive network. The PAN in the present invention is used as both an adhesive and a conductive agent. If a high heat treatment temperature is used, the PAN will be completely carbonized to form a carbon material, which can only be used as a conductive agent, but cannot play the role of an adhesive.

[0021] More preferably, in step S3, during the mixing process, the speed of magnetic stirring is 500-700 rpm, and the stirring time is 10-12 h.

[0022] More preferably, in step S3, the drying temperature is 80-100° C. and the drying time is 10-12 hours.

[0023] Preferably, in step S3, the scraper thickness is 100-300 μm, and the loading amount of the slurry on the copper foil is 2 mg cm -2 ~8mg cm -2 .

[0024] The second aspect of the present invention provides a lithium ion battery silicon-based negative electrode sheet, which is prepared by the above-mentioned preparation method, wherein the surface of the nano-silicon is coated with an inorganic fast ion conductor layer and an organic conductive polymer cracking layer in sequence, wherein the inorganic fast ion conductor layer is a Li-ion conductive layer in situ generated on the surface of the nano-silicon by a sol-gel method. 1.3 Al 0.3 Ti 1.7 The (PO4)3 coating layer and the organic conductive polymer cracking layer are carbon coating layers prepared by liquid phase coating and low temperature cyclization process.

[0025] Therefore, the present invention adopts a lithium-ion battery silicon-based negative electrode sheet and a preparation method thereof with the above structure, which has the following beneficial effects:

[0026] (1) The present invention constructs a uniform double coating layer on the surface of nano-silicon by a sol-gel and low-temperature cyclization method, and the coating layer is composed of an inorganic fast ion conductor layer and an organic conductive polymer cracking layer. Among them, the inorganic substance has a strong covalent bond, which can provide high structural stability for the core Si. At the same time, the inorganic substance also has high ion conductivity, which is conducive to the diffusion of lithium ions in the electrode material. In addition, through the low-temperature cyclization reaction, the conductive polymer exhibits high oxidation resistance and can fill the gaps between the inorganic coated particles, relieve the stress generated by the volume expansion of silicon during the charge and discharge process, and maintain the structural integrity.

[0027] (2) In the process of preparing the negative electrode sheet of the present invention, the conductive polymer acts as both a binder and a conductive agent, and adheres to the entire surface of the nano-silicon particles by in-situ polymerization, thereby forming a more stable conductive network. This design of integrating the negative electrode material with the electrode sheet can not only slow down the side reactions at the interface, but also significantly enhance the electron transmission between the interconnected Si nanoparticles, thereby improving the electrochemical performance of the battery.

[0028] (3) The outer carbon layer in the present invention can be used to fill the gaps between the LATP coated particles, isolate the physical contact between the electrode and the electrolyte, and slow down the occurrence of interfacial side reactions. In addition, unlike the point contact between conventional conductive carbon and silicon materials, PAN adheres to the entire surface of the Si particles by in-situ cyclopolymerization, thereby forming a more stable conductive network. The organic / inorganic double-layer coating of the present invention cleverly enhances the electron and ion transmission between the interconnected Si particles, thereby improving the electrochemical performance of the battery.

[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a flow chart of the preparation of the negative electrode sheet of Example 1;

[0031] Figure 2The flowchart of the preparation of the negative electrode sheet of Example 2;

[0032] Figure 3 SEM images of nano-silicon and Si@LATP@C-1 negative electrode sheet prepared in Example 1;

[0033] Figure 4 TEM image of the Si@LATP@C-1 negative electrode sheet prepared in Example 1;

[0034] Figure 5 EDS image of the Si@LATP@C-1 negative electrode sheet prepared in Example 1

[0035] Figure 6 X-ray diffraction patterns of the negative electrode sheets prepared in Comparative Examples 1 to 3 and Example 1;

[0036] Figure 7 This is the X-ray photoelectron spectrum of the Si@LATP@C-1 negative electrode sheet prepared in Example 1;

[0037] Figure 8 EIS impedance spectra of the negative electrode sheets prepared in Comparative Examples 1 to 4 and Examples 1 to 2;

[0038] Fig. 9 The first 500 cycle stability diagrams of the negative electrode sheets prepared in Comparative Examples 1 to 4 and Examples 1 to 2 when the current density is 1 A / g;

[0039] Fig.10 The figure is a rate performance diagram of the negative electrode sheets prepared in Comparative Examples 1 to 4 and Examples 1 to 2 at different current densities. DETAILED DESCRIPTION

[0040] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0041] Example 1

[0042] like Figure 1 As shown, a method for preparing a lithium-ion battery silicon-based negative electrode sheet (Si@LATP@C-1) comprises the following steps:

[0043] Step 1: Preparation of Nano-Si:

[0044] Commercial silicon powder was added into a planetary ball mill and subjected to high-energy ball milling at a speed of 400 rpm for 12 h to obtain nano-Si with a particle size of 100 to 200 nm.

[0045] Step 2: Preparation of 2% LATP coated Si negative electrode material (Si@2% LATP):

[0046] First, LiNO3, Al(NO3)3·9H2O, and C 12 H 28 O4Ti and H3PO4 were dissolved in 10 ml of anhydrous ethanol to form a LATP precursor solution, and then 1 g of nano-Si was added to the solution, ultrasonically dispersed for 1 h, and magnetically stirred at 70 ° C for 10 h to completely evaporate the solvent. 12 H 28 The total mass of O4Ti, H3PO4 and Si is 100 equal parts, and the mass of Si accounts for 98 equal parts.

[0047] Finally, the solid sample collected after evaporating the solvent was placed in a corundum boat, transferred to a tube furnace, and heated to 650°C at a heating rate of 5°C / min under Ar atmosphere and kept warm for 4 hours. After the reaction was completed, it was naturally cooled and ground into fine powder to obtain Si@2%LATP negative electrode material.

[0048] Step 3: Preparation of 2% LATP and C double-layer coated Si negative electrode material (Si@LATP@C-1):

[0049] Si@2%LATP@C was prepared by liquid phase coating method. The specific process is as follows:

[0050] First, Si@2%LATP negative electrode material and PAN were fully mixed in a mass ratio of 7:3, dissolved in 2mL DMF, and magnetically stirred for 10h to form a slurry. Then, the slurry was scraped onto copper foil using a scraper and dried in a vacuum drying oven at 80°C for 12h to completely evaporate the solvent. Finally, the electrode was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min in an Ar atmosphere. The temperature was kept for 2h, and after cooling to room temperature, the Si@LATP@C-1 negative electrode sheet was obtained.

[0051] The Si@LATP@C-1 negative electrode sheet prepared in Example 1 was characterized by SEM. Figure 3 It can be seen that the particle size of the nano-silicon obtained by ball milling is about 100-200nm. After double-layer coating, the surface of the nano-silicon still presents irregular particle morphology, and the average particle size increases to 200-300nm, indicating that the inorganic matter of LATP and the organic carbon layer formed by polyacrylonitrile have been successfully coated on the surface of the nano-silicon.

[0052] The Si@LATP@C-1 negative electrode sheet prepared in Example 1 was characterized by TEM. Figure 4 It can be seen that the surface of the Si@LATP@C-1 negative electrode material has an obvious carbon layer and (042) lattice fringes of LATP, indicating that LATP and the organic carbon layer have been successfully coated on the surface of nano-silicon.

[0053] The Si@LATP@C-1 negative electrode sheet prepared in Example 1 was characterized by EDS. Figure 5 It can be seen that the negative electrode material prepared in Example 1 contains Si, Al, O, P, C and Ti elements, indicating that the Si@LATP@C negative electrode material has been successfully synthesized.

[0054] The Si@LATP@C-1 negative electrode sheet prepared in Example 1 was characterized by XPS. Figure 7 It can be seen that the negative electrode material prepared in Example 1 contains Si, O, P, C and Ti elements, indicating that the Si@LATP@C-1 negative electrode material has been successfully synthesized.

[0055] Example 2

[0056] like Figure 2 As shown, a method for preparing a lithium-ion battery silicon-based negative electrode sheet (Si@LATP@C-2) comprises the following steps:

[0057] Step 1: Preparation of Nano-Si:

[0058] Commercial silicon powder was added into a planetary ball mill and subjected to high-energy ball milling at a speed of 400 rpm for 12 h to obtain nano-Si with a particle size of 100 to 200 nm.

[0059] Step 2: Preparation of 2% LATP coated Si negative electrode material (Si@2% LATP):

[0060] First, LiNO3, Al(NO3)3·9H2O, C 12 H 28 O4Ti and H3PO4 as well as nano-silicon were dissolved in 10 ml of anhydrous ethanol, LiNO3, Al(NO3)3·9H2O, C 12 H 28 The molar ratio of O4Ti and H3PO4 is 1.3:0.3:1.7:3, the mass of nano-Si added is 1g, ultrasonic dispersion is performed for 1h, and magnetic stirring is performed at 70℃ for 10h to completely evaporate the solvent. 12 H 28 The total mass of O4Ti, H3PO4 and Si is 100 equal parts, and the mass of Si accounts for 98 equal parts.

[0061] Finally, the solid sample collected after evaporating the solvent was placed in a corundum boat, transferred to a tube furnace, and heated to 650°C at a heating rate of 5°C / min under Ar atmosphere and kept warm for 4 hours. After the reaction was completed, it was naturally cooled and ground into fine powder to obtain Si@2%LATP negative electrode material.

[0062] Step 3: Preparation of 2% LATP and C double-layer coated Si negative electrode material (Si@LATP@C-2):

[0063] Si@LATP@C-2 was prepared using a liquid phase coating method. The specific process is as follows:

[0064] First, Si@2%LATP negative electrode material and PAN were fully mixed in a mass ratio of 7:3, dissolved in 2mL DMF, and magnetically stirred for 10 h to form a slurry. Then, the slurry was scraped onto copper foil using a scraper and dried in a vacuum drying oven at 80°C for 12 h to completely evaporate the solvent. Finally, the electrode was placed in a tubular furnace and heated to 300°C at a heating rate of 5°C / min in an Ar atmosphere. The temperature was kept for 2 h, and after cooling to room temperature, the Si@LATP@C negative electrode sheet was obtained.

[0065] Comparative Example 1

[0066] A method for preparing a lithium-ion battery silicon-based negative electrode sheet (Si@2% LATP), comprising the following steps:

[0067] Step 1: Preparation of Nano-Silicon (Si):

[0068] The silicon powder was added into a planetary ball mill and subjected to high-energy ball milling at a speed of 400 rpm for 12 hours to obtain nano-Si with a particle size of 100 to 200 nm.

[0069] Step 2: Preparation of 2% LATP coated Si negative electrode material (Si@2% LATP):

[0070] The LATP coating layer was constructed in situ on the surface of the Si negative electrode using the sol-gel method. The specific process is as follows:

[0071] First, LiNO3, Al(NO3)3·9H2O, and C 12 H 28 O4Ti and H3PO4 were dissolved in 10 ml of anhydrous ethanol to form a LATP precursor solution, and then 1 g of nano-Si was added to the solution, ultrasonically dispersed for 1 h, and then magnetically stirred at 70 ° C for 10 h to completely evaporate the anhydrous ethanol. 12 H 28 The total mass of O4Ti, H3PO4 and Si is 100 equal parts, and the mass of Si accounts for 98 equal parts.

[0072] The solid sample collected after evaporation of the solvent was placed in a corundum boat, transferred to a tube furnace, and heated to 650°C at a heating rate of 5°C / min under Ar atmosphere and kept warm for 4 hours. After the reaction was completed, it was naturally cooled and ground into fine powder to obtain Si@2%LATP negative electrode material.

[0073] Step 3: Mix the obtained Si@2%LATP negative electrode material with the conductive agent (Super P) and the binder polyacrylic acid (PAA) in a mass ratio of 8:1:1, dissolve in 2mL of deionized water and stir continuously for 12h to obtain a uniformly dispersed viscous slurry. Then, use a scraper to evenly coat the mixed slurry on the copper foil to obtain the electrode. Transfer the electrode to a vacuum drying oven at 80℃ and dry it for 12h to obtain a Si@2%LATP negative electrode sheet.

[0074] Comparative Example 2

[0075] A method for preparing a lithium-ion battery silicon-based negative electrode sheet (Si@4% LATP), comprising the following steps:

[0076] Step 1: Preparation of Nano-Si:

[0077] Commercial silicon powder was added into a planetary ball mill and subjected to high-energy ball milling at a speed of 400 rpm for 12 h to obtain nano-Si with a particle size of 100 to 200 nm.

[0078] Step 2: Preparation of 4% LATP coated Si negative electrode material (Si@2% LATP):

[0079] First, LiNO3, Al(NO3)3·9H2O, and C 12 H 28 O4Ti and H3PO4 were dissolved in 10 ml of anhydrous ethanol to form LATP precursor, and then 1 g of nano-Si was added to the solution, ultrasonically dispersed for 1 h, and magnetically stirred at 70 ° C for 10 h to completely evaporate the solvent. 12 H 28 The total mass of O4Ti, H3PO4 and Si is 100 equal parts, and the mass of Si accounts for 96 equal parts.

[0080] Finally, the solid sample collected after evaporating the solvent was placed in a corundum boat, transferred to a tube furnace, and heated to 650°C at a heating rate of 5°C / min under Ar atmosphere and kept warm for 4 hours. After the reaction was completed, it was naturally cooled and ground into fine powder to obtain Si@4%LATP negative electrode material.

[0081] Step 3: Mix the obtained Si@4%LATP negative electrode material with the conductive agent (Super P) and the binder polyacrylic acid (PAA) in a mass ratio of 8:1:1, dissolve in 2mL of deionized water and stir for 12h to obtain a uniformly dispersed viscous slurry. Then, use a scraper to evenly coat the mixed slurry on the copper foil. Transfer the electrode to a vacuum drying oven at 80℃ and dry it for 12h to obtain a Si@4%LATP negative electrode sheet.

[0082] Comparative Example 3

[0083] A method for preparing a Si-based negative electrode sheet comprises the following steps:

[0084] Step 1: Preparation of Nano-Si:

[0085] Commercial silicon powder was added into a planetary ball mill and subjected to high-energy ball milling at a speed of 400 rpm for 12 h to obtain nano-Si with a particle size of 100 to 200 nm.

[0086] Step 2: Mix the obtained nano-Si negative electrode material with the conductive agent (Super P) and the binder polyacrylic acid (PAA) in a mass ratio of 8:1:1, dissolve in 2mL of deionized water and stir for 12h to obtain a uniformly dispersed viscous slurry. Then, use a scraper to evenly coat the mixed slurry on the copper foil. Transfer the electrode to a vacuum drying oven at 80℃ and fully dry for 12h to obtain a Si negative electrode sheet.

[0087] XRD characterization was performed on Si@LATP@C-1 prepared in Example 1, Si@2%LATP prepared in Comparative Example 1, Si@4%LATP prepared in Comparative Example 2, and Si prepared in Comparative Example 3. Figure 6 It can be seen that the negative electrode materials prepared in Comparative Examples 1 to 3 and Example 1 all have characteristic peaks corresponding to the silicon standard card, but due to the small loading amount of LATP and polyacrylonitrile, their characteristic peaks are not shown.

[0088] Comparative Example 4

[0089] A method for preparing a lithium-ion battery silicon-based negative electrode sheet (Si@LATP@C-600), comprising the following steps:

[0090] Step 1: Preparation of Nano-Si:

[0091] Commercial silicon powder was added into a planetary ball mill and subjected to high-energy ball milling at a speed of 400 rpm for 12 h to obtain nano-Si with a particle size of 100 to 200 nm.

[0092] Step 2: Preparation of 2% LATP coated Si negative electrode material (Si@2% LATP):

[0093] First, LiNO3, Al(NO3)3·9H2O, and C 12 H 28 O4Ti and H3PO4 were dissolved in 10 ml of anhydrous ethanol to form a LATP precursor solution, and then 1 g of nano-Si was added to the solution, ultrasonically dispersed for 1 h, and magnetically stirred at 70 ° C for 10 h to completely evaporate the solvent. 12 H 28 The total mass of O4Ti, H3PO4 and Si is 100 equal parts, and the mass of Si accounts for 98 equal parts.

[0094] Finally, the solid sample collected after evaporating the solvent was placed in a corundum boat, transferred to a tube furnace, and heated to 650°C at a heating rate of 5°C / min under Ar atmosphere and kept warm for 4 hours. After the reaction was completed, it was naturally cooled and ground into fine powder to obtain Si@2%LATP negative electrode material.

[0095] Step 3: Preparation of 2% LATP and C double-layer coated Si negative electrode material (Si@LATP@C-600):

[0096] Si@LATP@C-600 was prepared by liquid phase coating method. The specific process is as follows:

[0097] First, Si@2%LATP negative electrode material and PAN were fully mixed at a mass ratio of 7:3, dissolved in 2mL DMF, and magnetically stirred for 10 hours to form a slurry. Then, it was dried at 80°C in a vacuum drying oven for 12 hours to completely evaporate the solvent. Finally, the obtained solid was placed in a tubular furnace and heated to 600°C at a heating rate of 5°C / min under an Ar atmosphere. The temperature was kept for 2 hours, and after cooling to room temperature, the Si@LATP@C-600 negative electrode material was obtained.

[0098] Step 4: Preparation of Si@LATP@C-600 negative electrode sheet:

[0099] The obtained Si@LATP@C-600 negative electrode material was mixed with a conductive agent (Super P) and a binder polyacrylic acid (PAA) at a mass ratio of 8:1:1, dissolved in 2m deionized water and stirred for 12h to obtain a uniformly dispersed viscous slurry. Then, a scraper was used to evenly coat the mixed slurry on the copper foil. The electrode was transferred to a vacuum drying oven at 80°C and fully dried for 12h to obtain a Si@LATP@C-600 negative electrode sheet.

[0100] In Comparative Example 4, since the heat treatment temperature of PAN in step 3 is increased, PAN is completely carbonized to form a carbon matrix, which fills the pores between the LATP inorganic particles in the first coating layer. PAN cannot act as a binder, and only the negative electrode material in the form of granular powder can be obtained, and the negative electrode sheet cannot be directly formed on the surface of the copper foil. Therefore, step 4 is required to prepare the negative electrode sheet, which increases the complexity of the reaction steps and affects the cycle performance of the negative electrode sheet to a certain extent.

[0101] Test example

[0102] The electrochemical performance tests were performed on the lithium-ion batteries of the embodiments and comparative examples. The test results are shown in Table 1.

[0103] Table 1 Electrochemical performance test results of negative electrode sheets of the embodiments and comparative examples

[0104]

[0105] From Table 1 and Figure 8 to Figure 10 It can be seen that the negative electrode sheet prepared in the embodiment is much better than the comparative example in charge transfer resistance, rate performance and cycle performance. Although the nano-Si has a charge transfer resistance of 3943.1 mAh g -1 However, as the number of cycles increases, the specific capacity of silicon decreases sharply, and after 500 cycles, it only maintains 745.9 mAh g -1 This is mainly due to poor conductivity and pulverization caused by severe volume change, resulting in poor cycle performance. After the LATP and C coating layers were introduced on the surface of Si particles, the first cycle discharge capacity of Si@LATP@C-1 was 3429.8 mAh g -1 After 500 cycles, the capacity can still be maintained at 1528.6 mAh g -1 Even at a high current density of 5A / g, the discharge capacity can still be maintained at 628.5mAh g -1 This is mainly because the high ion conductor LATP tightly wraps the silicon nanoparticles, which not only improves the ion conductivity of the silicon nanoparticles, but also effectively alleviates the volume expansion of the silicon nanoparticles. The external coating of the PAN-based cyclized carbon layer can further improve the stability of the electrode. The charge transfer resistance of the Si@LATP@C-1 electrode is 15.6Ω, which is 9.5 times lower than that of the Si electrode, indicating that the presence of LATP and C improves the electronic conductivity of the composite material. At the same time, the preparation of the negative electrode sheet of the present invention also has the advantages of low raw material cost and simple process, indicating that the Si@LATP@C negative electrode sheet has a good application prospect for lithium-ion batteries.

[0106] Therefore, the present invention adopts the above-mentioned lithium-ion battery silicon-based negative electrode sheet and its preparation method to construct a uniform LATP / C mixed coating on the surface of nano Si particles. The ions in the mixed coating layer are mainly transmitted through LATP, and an excessively thick LATP coating layer will inhibit the capacity. In the preparation process of the negative electrode sheet, PAN is used as both a binder and a conductive agent, and adheres to the entire surface of the silicon particles by in-situ polymerization. Under low-temperature heat treatment conditions, a cyclization reaction occurs, and the formed carbon layer has a high electronic conductivity, which promotes electronic conduction in the composite negative electrode. The synergistic effect of LATP / C can effectively alleviate the side reactions at the interface between the electrode and the electrolyte, inhibit the volume change of the silicon negative electrode during the cycle, and strengthen the transmission process of ions and electrons in the negative electrode. The negative electrode exhibits excellent electrochemical properties and is considered to be an ideal negative electrode material for lithium-ion batteries.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a lithium-ion battery silicon-based negative electrode sheet, characterized in that: The following steps are involved: S1: Add silicon powder into a ball mill and grind to obtain nano silicon; S2: Nano-silicon and Li 1.3 Al 0.3 Ti 1.7 The raw materials of (PO4)3 are mixed in a solvent, and after mixing, they are heated and stirred until the solvent is completely evaporated, and the obtained solid sample is heat-treated to obtain a Si@LATP single-layer coating material; S3: The Si@LATP single-layer coating material and polyacrylonitrile are fully mixed in a solvent to obtain a slurry, and then the slurry is scraped onto a copper foil using a scraper, dried to completely evaporate the solvent, and then heat treated to obtain a Si@LATP@C negative electrode sheet.

2. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S1, the silicon powder is at least one of industrial waste silicon, micron-sized silicon powder, and nano-sized silicon powder; the particle size of nano-silicon is 100-200 nm; during the ball milling process, the mass ratio of ball milling beads to silicon powder is (15-20):1, the ball milling speed is 400-600 rpm, and the ball milling time is 10-12 hours.

3. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S2, nano-silicon and Li 1.3 Al 0.3 Ti 1.7 The specific process of mixing the raw materials of (PO4)3 in the solvent is as follows: LiNO3, Al(NO3)3·9H2O, C 12 H 28 O4Ti and H3PO4 are dissolved in anhydrous ethanol and magnetically stirred at room temperature to obtain a LATP precursor solution. Nano-silicon is then added to the LATP precursor solution, ultrasonically stirred to evenly disperse the nano-silicon in the solution, and then heated and magnetically stirred until the anhydrous ethanol is completely evaporated.

4. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S2, nano-silicon and Li 1.3 Al 0.3 Ti 1.7 The specific process of mixing the raw materials of (PO4)3 in the solvent is as follows: LiNO3, Al(NO3)3·9H2O, C 12 H 28 O4Ti, H3PO4 and nano-silicon are dissolved in anhydrous ethanol, and magnetic stirring is performed at room temperature combined with ultrasound to make the nano-silicon dispersed evenly in the solution, and then heating and magnetic stirring are performed until the anhydrous ethanol is completely evaporated.

5. A method for preparing a lithium-ion battery silicon-based negative electrode sheet according to any one of claims 3 or 4, characterized in that: In step S2, LiNO3, Al(NO3)3•9H2O, C 12 H 28 The molar ratio of O4Ti and H3PO4 is 1.3:0.3:1.7:3; LiNO3, Al(NO3)3•9H2O, C 12 H 28 The mass ratio of the total mass of O4Ti and H3PO4 to nano-silicon is (1~10):(90~99).

6. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S2, the heat treatment temperature is 600-800°C, the heating rate is 3-8°C / min, and the holding time is 3-5 h.

7. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S3, the mass ratio of Si@LATP single-layer coating material to polyacrylonitrile is (2-4):

1.

8. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S3, the heat treatment temperature is 250-350°C, the heating rate is 3-8°C / min, and the holding time is 1-3 h.

9. The method for preparing a lithium-ion battery silicon-based negative electrode sheet according to claim 1, characterized in that: In step S3, the scraper thickness is 100-300 μm, and the slurry loading on the copper foil is 2 mg cm -2 ~8 mg cm -2 .

10. A lithium-ion battery silicon-based negative electrode sheet, characterized in that: The nano-silicon is prepared by the preparation method according to any one of claims 1 to 9, wherein the surface of the nano-silicon is sequentially coated with an inorganic fast ion conductor layer and an organic conductive polymer cracking layer, wherein the inorganic fast ion conductor layer is Li generated in situ on the surface of the nano-silicon by a sol-gel method. 1.3 Al 0.3 Ti 1.7 The (PO4)3 coating layer and the organic conductive polymer cracking layer are carbon coating layers prepared by liquid phase coating and low temperature cyclization process.